Non-linear models of employment adjustment - Werner Smolny (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1993)
The paper deals with causes and consequences of constraints on the adjustment of employment. First, a model of a delayed adjustment of employment and capital is worked out. This model is augmented with linear constraints on the adjustment speed of labour supply and demand. The aggregate model is estimated for the Federal Republic of Germany. The results confirm the importance of adjustment barriers for the employment situation in the FRG. especially for the persistence of unemployment in the second half of the eighties. Final estimates of a non-linear error correction model give a hint on non-linearities of observed employment adjustments.
Keywords: 330; Arbeitsmarkttheorie; Rationierung; Arbeitslosigkeit; Theorie; Deutschland